Employment challenges to the knowledge economy in Europe: the case of IT services. (1st April 2010) - ,; ,; ,; ,
Abstract : This paper investigates the employment challenges facing the fast-expanding IT services sector in Europe and contributes to debates about what policy reforms are required to nurture the so-called knowledge economy. The IT services sector is highly internationalised and strongly concentrated in all the four countries examined - Austria, France, Germany, and the UK. Nevertheless, policy reform is unlikely to follow a universal route, since the development of IT services has been strongly shaped by its interaction with each country's specific national employment model. The article investigates three employment challenges, namely the country system of skill formation, forms of collective employee and employer representation, and patterns of worker mobility and use of non-standard employment contracts. While important, national employment models do not determine the character of the sector and the paper identifies several points of tension and contradiction that raise questions about the future sustainability of knowledge economy sectors.